Developing Language and Communication Skills in Foreign Language Learning via Digital Resources for Reading (a Study of Storyweaver, Project Gutenberg, Manybooks) - Sheludchenko , Svitlana; Karaim , Anna Mariia (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2025)
Relevance. The article explores the potential of the digital platforms, namely StoryWeaver, Project Gutenberg and ManyBooks, as tools for the formation and development of linguistic and communicative competencies in the process of foreign language learning. In the context of the digitalization in the sphere of education, online resources that provide free access to a variety of original language reading texts are gaining increasing popularity. These platforms contain a large number of textual materials that represent various genres, levels of complexity, and topics. The platforms contribute to their effective adaptation to the needs of learners with different levels of language proficiency. The purpose of the study is to analyze the potential of the digital reading resources StoryWeaver, Project Gutenberg, and ManyBooks in developing linguistic and communicative competences in foreign language learning.Research results. In the course of the research, the possibilities of using these resources as a didactic tool that promotes the expansion of vocabulary, the improvement of grammatical skills, the enhancement of reading and translation abilities, as well as the development of critical and creative thinking, were analyzed. The authors emphasize the importance of working with original texts as such materials allow students to better immerse themselves in the linguistic and communicative environment, understand cultural contexts, and the peculiarities of foreign language discourse. The involvement of digital platforms in the educational process also stimulates motivation for independent learning, increases the level of engagement of learners, and contributes to the formation of self-regulated learning skills.Particular attention has been paid to the integration of these online resources into the learning process as an element of modern pedagogical strategy. The study demonstrates the examples of how to work with the texts that educators can use to develop various components of language competence. The advantages and challenges associated with the use of the digital resources under investigation in the field of education and pedagogy are also analyzed. It is concluded that the platforms (StoryWeaver, Project Gutenberg and ManyBooks) are effective tools for improving the quality of linguistic and communicative training, contribute to the creation of a more flexible and inclusive educational environment, and open up new perspectives for foreign language learning in the digital era.